PENGARUH BRAND AWARENESS DAN BRAND LOYALTY TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT - Sherli Indah Lestari; Sugeng Prayetno; Joni Tesmanto (Bajang Institute, 2025)
This study aims to analyze the effect of Brand Awareness and Brand Loyalty on Purchasing Decisions for SCARLETT products. The method used is quantitative. The sample in this study amounted to 100 respondents who were consumers of SCARLETT products. The data collection technique was carried out through a questionnaire and analyzed using validity, reliability, multiple linear regression, t test, F test, and the coefficient of determination (R²). The research results identify that all items on the Brand Awareness, Brand Loyalty, and Purchase Decision variables have a correlation value above 0.30 with a significance of <0.05, which means they are valid. The reliability test results with Cronbach Alpha> 0.60 also show that all instruments used are reliable. Multiple linear regression analysis results in the equation Y = 9920.163 + 0.216X1 + 0.712X2, which shows that both Brand Awareness (X1) and Brand Loyalty (X2) have a positive effect on Purchasing Decisions (Y). The t test results show that Brand Awareness has a significant effect (p = 0.040 ≤ 0.05), and Brand Loyalty has a very significant effect (p = 0.000 ≤ 0.05) with a beta value of 0.741, the F test produces a significance value of 0.000 (<0.05), which means that Brand Awareness and Brand Loyalty simultaneously have a significant effect on Purchasing Decisions. The coefficient of determination (R²) of 0.711 indicates that 71.1% of the Purchasing Decision variable can be explained by Brand Awareness and Brand Loyalty, while the remaining 28.9% is influenced by other variables outside this study